2016
DOI: 10.4103/0253-7613.186212
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals, antioxidant, and anthelmintic activity of selected traditional wild edible plants of lower Assam

Abstract: Objective:Clerodendrum viscosum, Eryngium foetidum, Lippia javanica, and Murraya koenigii are one among the common wild edible plants in Northeast India which are also used as antidiabetic, stomach-ache relieving drugs, etc., The present study was aimed to reveal the phytochemical, antioxidant, and anthelmintic activity of the plants.Materials and Methods:The antioxidant capacity of methanolic extract of plants was studied by 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power, TBARS, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…16 Medicinal properties of plants depend on their phytochemical constituents such as steroids, saponin, alkaloids, terpenoids, phenol, proanthocyanidins and tannin. 6 In this study, Lippia Javanica was confirmed to consist of tannin, flavonoids, terpenoids, alkaloids and phenols. This finding corroborated with previous reports on phytochemical screening of Lippia Javanica.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…16 Medicinal properties of plants depend on their phytochemical constituents such as steroids, saponin, alkaloids, terpenoids, phenol, proanthocyanidins and tannin. 6 In this study, Lippia Javanica was confirmed to consist of tannin, flavonoids, terpenoids, alkaloids and phenols. This finding corroborated with previous reports on phytochemical screening of Lippia Javanica.…”
Section: Discussionmentioning
confidence: 58%
“…18 Flavonoid tremendous activities include; anti-viral, anti-inflammatory, anti-bacterial, and anti-oxidant. 6 Alkaloids, Terpenes and Tannin have also been reported to possessed anticancer, antioxidant, anti-pyretic, with different alphabets (a, b, c, d) were significant (p < 0.05). anti-inflammatory, antidiabetic, anti-platelet aggregation and sedative activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flavonoids are important secondary metabolite that possesses tremendous medicinal property such as antioxidant, antiinflammatory, anticancer, antibacterial, anti-viral activity etc [29]. The phytochemicals screening of methanolic extracts of A. calamus (MeAc), H. rosa-sinensis (MeHr), C. dactylon (MeCd) and E. floribundus (MeEf) showed high content of carbohydrates and proteins (table 1).…”
Section: Phytochemical Analysismentioning
confidence: 99%